Entrance of Castries, St. Lucia. Harbour and town. - (:unkn) unknown (My University, 2012)
The post card depicts an aerial view of the St. Lucia harbour and town. Ships can be seen in the bay by the capital Castries. The town is built up with many buildings. On the front of the postcard: M and C 31. The back reads St. Lucia (Ste. Lucie). There is a duplicate postcard pc 97.
Landscape; black and white
Keywords: Aerial views; Bays (Bodies of water); Landscapes (Representations); Postcards